The Eyes of the Nation : Perspectives on Israeli Art of the Seventies - Visual Art in a Country Without Boundaries. - Fischer, Yona; Getter, Tamar; Geva, Avital; Ginton, David; Ginton, Ellen; Keren, Sharon; Na'aman, Michal; Ofrat, Gideon; Omer, Mordechai; Ram, Uri; Scheps, Marc (Tel Aviv : Tel Aviv Museum of Art, 1998)
Ullman, Micha ; Or-Ner, Dov ; Berest, Dganit ; Geva, Avital ; Goldstein, Zvi ; Getter, Tamar ; Gechtman, Gideon ; Garbuz, Yair ; Gershuni, Moshe ; Druks, Michael ; Weinfeld, Yocheved ; Gan, Pinchas Cohen ; Levin, Yudith ; Mizrachi, Motti ; Maor, Haim ; Na'aman, Michal ; Neustein, Joshua ; Natan, Efrat ; Klasmer, Gabi ; Keren, Sharon
biografie, bibliografie
The Eyes of the Nation : Perspectives on Israeli Art of the Seventies - Visual Art in a Country Without Boundaries, Tel Aviv Museum of Art, Tel Aviv, Joseph and Rebecca Meyerhoff Pavilion, 7 April - 30 May, 1998
Engels & Hebreeuws
kunstcatalogus
Keywords: Israel